2009
DOI: 10.1002/btpr.377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of freezing on pH of buffered solutions and consequences for monoclonal antibody aggregation

Abstract: Freezing of biologic drug substance at large scale is an important unit operation that enables manufacturing flexibility and increased use-period for the material. Stability of the biologic in frozen solutions is associated with a number of issues including potentially destabilizing pH changes. The pH changes arise from temperature-associated change in the pK(a)s, solubility limitations, eutectic crystallization, and cryoconcentration. The pH changes for most of the common protein formulation buffers in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 31 publications
4
83
0
2
Order By: Relevance
“…Alternative buffers to carboxylic acids which are known to have minor to moderate pH changes (around one pH unit change) during freezing include histidine and Tris [25]. The temperature-pH profile of 20 mM histidine has been studied and shown to have less than one pH unit increase (5.4 to 6.1) upon freezing to − 30 °C [25].…”
Section: Amines and Amino Acidsmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternative buffers to carboxylic acids which are known to have minor to moderate pH changes (around one pH unit change) during freezing include histidine and Tris [25]. The temperature-pH profile of 20 mM histidine has been studied and shown to have less than one pH unit increase (5.4 to 6.1) upon freezing to − 30 °C [25].…”
Section: Amines and Amino Acidsmentioning
confidence: 98%
“…The temperature-pH profile of 20 mM histidine has been studied and shown to have less than one pH unit increase (5.4 to 6.1) upon freezing to − 30 °C [25]. The crystallization behavior of histidine during freeze/thaw has been shown to be pH dependent [35].…”
Section: Amines and Amino Acidsmentioning
confidence: 98%
“…Several buffer systems such as Tris-HCl and sodium phosphate have large dpKa/ dT, which can result in change in pH during cooling and freezing. Recent studies have suggested that pH changes due to buffer during cooling and freezing can be ruled out as a factor in aggregation behavior (Kolhe, Amend, & Singh, 2010). However, buffer systems where the pH changes due to crystallization of a buffer salt upon freezing can impact protein conformation as shown by studies on the freeze-drying of γ interferon (Lam, Costantino, Overcashier, Nguyen, & Hsu, 1996).…”
Section: Freezing and Thawingmentioning
confidence: 99%
“…In a relatively narrow pH range, IgG1 aggregates were shown to grow primarily by monomer addition and remained small and soluble at pH 3.5 but grew by both chain polymerization and condensation and become large and insoluble at pH 4.5 and higher pH (36). Changing temperature also changes the pH of certain formulation buffers due to temperature-dependent changes in the degree of ionization (74). Chemical degradation could lead to formation of basic or acidic species, altering the solution pH, such as deamidation of asparagines (75).…”
Section: Temperature-dependent Change In Aggregation Mechanisms or Somentioning
confidence: 99%